2020
DOI: 10.1002/adma.202003404
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor

Abstract: The structure and packing of organic mixed ionic-electronic conductors have an especially significant effect on transport properties. In operating devices, this structure is not fixed but is responsive to changes in electrochemical potential, ion intercalation, and solvent swelling. Toward this end, the steadystate and transient structure of the model organic mixed conductor, poly(3,4ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), is characterized using multimodal time-resolved operando techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 43 publications
(45 reference statements)
8
97
0
Order By: Relevance
“…Several factors can contribute to this effect. First, the bipolarons induce structural changes in polythiophene films (as has been observed in-situ for electrochemical PEDOT:PSS reduction), 30 which might lead to better packing and short-range conductivity compared to -0.6 V, where a non-negligible fraction of neutral sites (~20%) add conformation barriers and localize the charges. The infiltration of counterions into the crystalline regions of P3HT at high doping levels can cause a similar morphological increase of the mobility, as has been reported in electrochemically doped polymers gated with an ionic liquid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors can contribute to this effect. First, the bipolarons induce structural changes in polythiophene films (as has been observed in-situ for electrochemical PEDOT:PSS reduction), 30 which might lead to better packing and short-range conductivity compared to -0.6 V, where a non-negligible fraction of neutral sites (~20%) add conformation barriers and localize the charges. The infiltration of counterions into the crystalline regions of P3HT at high doping levels can cause a similar morphological increase of the mobility, as has been reported in electrochemically doped polymers gated with an ionic liquid.…”
Section: Resultsmentioning
confidence: 99%
“…13 In-situ electrochemical strain microscopy on OECT devices distinguishes between surface and volumetric doping by probing even sub-nanometer changes in the polymer film thickness. 29 The role of polymer swelling from water and anions in mixed conductors containing hydrophilic glycolated side chains was accessed via in-situ electrochemical quartz crystal microbalance monitoring, 15,16 while structural changes during electrochemical reactions can be addressed by in-situ x-ray scattering experiments, 30 and in-situ spectroelectrochemistry allows to determine the presence of different polymer redox species. 18,30,31 We now add in-situ THz spectroscopy to this palette, since this measures the short-range charge transport properties, 32,33 which have been far less discussed than the long-range transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 ). Consistent with HRS P-50% PTHF, operando PEDOT:PSS measurements have also shown a lamellar expansion upon dedoping 47 , which indicates electrical stability of the HRS in non-volatile P-50% PTHF should be coupled with a long-lived structural modification. In addition, (020)* and (110)* peaks of PTHF in P-80% PTHF are unchanged in both LRS and HRS (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…21,42 Other factors include possible changes in the PSS binding site local environment that might occur during doping/dedoping, resulting in changes in  Since the measured residual value of , 〈 ̅ 〉, is also affected by the shape of the PEDOT-rich domains (as illustrated in Figure S12), the hysteresis may be caused by microstructural changes of the PEDOT:PSS (quantified via the order parameter, S) during electrochemical biasing, such as film swelling due to changes in water content. Other phenomena might be important: for example, Paulsen et al 43 recently reported an unsymmetric rate of structural change of PEDOT:PSS during doping and dedoping by operando X-ray scattering, ascribing the transient structural behaviour to the complex polaron-bipolaron dynamics that affects electronic charge carrier dynamics.…”
Section: Origin Of the Hysteresismentioning
confidence: 99%